The Young Person's Guide to Writing Economic Theory - Thomson, William (Journal of Economic Literature, 1999)
I formulate recommendations to young authors for writing economic theory well. I state general principles of good writing, and emphasize the role of the different components of a paper and the importance of the structure of one's work being clear. I explain how to choose notation and language, and how to present and illustrate proofs.